Wave-absorbing powder based on O2 <-> and Mo5 < + > step-by-step hybrid natural molybdenite and preparation method of wave-absorbing powder

The preparation of MoO2/MoS2 composite materials through O2- and Mo5+ step-by-step hybrid natural molybdenumite solves the problems of high cost and small application scope in the existing technology, realizes a low-cost, simple and safe process flow, and prepares excellent MoO2/MoS2 composite materials with electromagnetic wave absorption characteristics are suitable for a wide range of electromagnetic wave protection fields.

CN119143180APending Publication Date: 2024-12-17ZHENGZHOU UNIVERSITY OF AERONAUTICS +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411289750.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing processes are costly and have small application scope, complex operation and limited sample size, so it cannot guarantee the uniformity of the material and efficient electromagnetic wave absorption performance.

Method used

Using O2- and Mo5+ step-by-step hybrid natural molybdenumite, the MoO2/MoS2 composite absorbing material is prepared through heat treatment and MoCl5 doping, and the multi-sample sintering is performed using a muffle furnace and a drying box to simplify the process flow, reduce costs, and increase Electromagnetic wave absorption characteristics of the material.

Benefits of technology

A low-cost, simple and safe process is achieved, and MoO2/MoS2 composite materials with excellent electromagnetic wave absorption characteristics are prepared. They are suitable for a wide range of electromagnetic wave protection fields. They have good product consistency and can effectively absorb electromagnetic waves and cover multiple frequency ranges.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143180A_ABST
    Figure CN119143180A_ABST
Patent Text Reader

Abstract

The invention discloses wave-absorbing powder based on O2 <-> and Mo < 5 + > step-by-step hybridization of natural molybdenite and a preparation method of the wave-absorbing powder, and relates to the technical field of wave-absorbing materials.The method comprises the steps that 1, molybdenite is placed in a muffle furnace to be subjected to heat treatment, and an O-MoS (2-x) composite material is obtained; 2) uniformly stirring the composite material obtained in the step 1) and MoCl5 in deionized water; (3) putting the mixture obtained in the step (2) into a drying box and staying overnight until the mixture is dried; and 4) carrying out heat treatment on the dry mixture obtained in the step 3) in a tubular furnace in an Ar atmosphere, and cooling the natural furnace to room temperature to obtain the MoO2 / MoS2 composite wave-absorbing material. Natural molybdenite is used as a stable raw material, MoCl5 is used as a doping substance, and the MoO2 / MoS2 composite wave-absorbing material is prepared through a simple heat treatment process with MoS2, so that the cost is low, the process flow is relatively simple and safe, and the product consistency is good; and the prepared MoO2 / MoS2 composite wave-absorbing material has a better electromagnetic wave absorbing characteristic, and can be widely applied to the corresponding electromagnetic wave protection field as an electromagnetic wave absorbing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wave absorbing materials, and specifically relates to a wave absorbing material based on O 2- and Mo 5+ The invention discloses microwave absorbing powder of step-by-step hybridization of natural molybdenite and a preparation method thereof. Background Art

[0002] In the 5G era, various electronic devices are becoming more and more popular and are now common in our daily lives, such as mobile phones, microwave ovens, high-voltage transmission lines, signal towers, etc. While diverse electronic devices provide great convenience for our lives, they also bring many negative effects. For example, electromagnetic interference (EMI) radiation, as a derivative of the information age, not only affects the stability and accuracy of equipment, but also affects human health. When the plane takes off, the electromagnetic waves from the mobile phone will interfere with the internal system of the aircraft and affect normal takeoff. More importantly, if the human body is in an electromagnetic environment for a long time, it will experience health problems such as dizziness and memory loss. Therefore, in order to minimize electromagnetic radiation pollution, high-performance electromagnetic shielding materials have received widespread attention and have been widely used in aerospace, transportation, mobile communications, medical care, national defense and military fields.

[0003] MoS2 has a graphite-like layered structure that can be adjusted at the nanoscale. This structure provides rich interfaces and interlayer interactions, which helps improve its electromagnetic wave absorption performance. The conductivity of MoS2 varies with the number of layers and doping state. By adjusting its conductivity, the electromagnetic wave absorption capacity of MoS2 in different frequency ranges can be optimized.

[0004] Chinese patent publication CN106898691A provides a method for preparing oxygen-doped molybdenum disulfide thermoelectric materials, which improves the conductivity of molybdenum disulfide without reducing the Seebeck coefficient of molybdenum disulfide, and can effectively reduce the thermal conductivity, ultimately greatly improving the thermoelectric performance of the material. However, this patent has the following shortcomings: first, the cost is relatively high; second, when spark plasma sintering is used, the sample size is limited and is only suitable for smaller samples; third, the operation and optimization process is relatively complicated, and the uniformity of the sample cannot be guaranteed. . Summary of the invention

[0005] The object of the present invention is to provide a method based on 2- and Mo 5+ The microwave absorbing powder of step-by-step hybridization of natural molybdenite and the preparation method thereof solve the problems of high cost and small application scope of the existing process.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: a 2- and Mo 5+The method for preparing microwave absorbing powder by step-by-step hybridization of natural molybdenite is characterized by comprising the following steps:

[0007] 1) Place molybdenite in a muffle furnace for heat treatment to obtain O-MoS (2-x) Composite materials;

[0008] 2) stirring the composite material obtained in step 1) and MoCl5 in deionized water;

[0009] 3) placing the mixture obtained in step 2) in a drying oven overnight until dry;

[0010] 4) The dried mixture obtained in step 3) is heat treated in a tubular furnace in an Ar atmosphere and naturally cooled to room temperature to obtain a MoO2 / MoS2 composite absorbing material.

[0011] A further solution is that the heat treatment temperature in step 1) is 400-500° C. and the heat treatment time is set to 2-4 hours.

[0012] A further solution is that the mass ratio of the molybdenite, MoCl5 and deionized water is 1:0.5 to 1.5:10.

[0013] A further solution is that the stirring in step 2) is magnetic stirring, the speed is 150-180 rpm, and the stirring time is 30-60 min.

[0014] A further solution is that the temperature of the drying oven in step 3) is 80-100° C. and the drying time is 8-16 hours.

[0015] A further solution is that in step 4), the temperature is raised to the calcination temperature at a heating rate of 5 to 10°C / min, the heat treatment temperature is 700 to 900°C, and the holding time is 6 to 8 hours.

[0016] A further solution is to use natural molybdenite as raw material and heat treat it. 2- and Mo 5+ The natural molybdenite is hybridized step by step to realize the preparation of MoO2 / MoS2 composite absorbing material, which is then used as an electromagnetic wave absorbing material.

[0017] Advantages of the present invention:

[0018] (1) The present invention utilizes natural molybdenite as a stable raw material, MoCl5 as a doping substance and MoS2 through a simple heat treatment process to realize the preparation of MoO2 / MoS2 composite absorbing material, which has low cost, relatively simple and safe process flow, and good product consistency; and the prepared MoO2 / MoS2 composite absorbing material has better electromagnetic wave absorption characteristics, and can be widely used as an electromagnetic wave absorbing material in the corresponding electromagnetic wave protection field.

[0019] (2) The present invention utilizes a tubular furnace in an Ar atmosphere for sintering, which is relatively simple and safe to operate, saves costs, and can sinter multiple samples simultaneously. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 XRD patterns of MoO2 / MoS2-0.5, MoO2 / MoS2-1, and MoO2 / MoS2-1.5 composites;

[0021] Figure 2 This is a diagram showing the wave absorption performance of the MoO2 / MoS2-0.5 composite material of Example 1 of the present invention.

[0022] Figure 3 This is a diagram showing the wave absorption performance of the MoO2 / MoS2-1 composite material of Example 2 of the present invention.

[0023] Figure 4 This is a diagram showing the wave absorption performance of the MoO2 / MoS2-1.5 composite material of Example 3 of the present invention.

[0024] Figure 5 This is a diagram of the wave absorption performance of the MoO2 / MoS2-800 composite material of Control Example 1 of the present invention.

[0025] Figure 6 This is a diagram of the wave absorption performance of the MoO2 / MoS2-900 composite material of Control Example 2 of the present invention.

[0026] Figure 7 This is a diagram showing the wave absorption performance of the MoO2 / MoS2-900-1 composite material of control example 3 of the present invention.

[0027] Figure 8 This is a diagram of the wave absorption performance of the MoS2-2 composite material of control example 4 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0029] The following examples are only used to further illustrate the present invention, but do not constitute any limitation to the present invention; the materials used in the following examples are natural molybdenite, main component: MoS2 (2H phase), purity: ≥96%, origin: Xumu Mountain, Myanmar. Other materials, unless otherwise specified, were purchased from conventional chemical reagent companies and raw material suppliers.

[0030] Example 1

[0031] A based on O 2- and Mo 5+ The microwave absorbing powder of step-by-step hybridization of natural molybdenite and the preparation method thereof comprise the following steps:

[0032] (1) 2 g of molybdenite powder was placed in a small porcelain boat and heat treated in a muffle furnace. The heat treatment temperature was 400°C and the heat treatment time was set to 2 h.

[0033] (2) The heat-treated mixture and 0.5 g MoCl5 were added to 10 ml deionized water and magnetically stirred for 30 min at a speed of 180 rpm.

[0034] (3) The obtained mixture was placed in a drying oven at 80°C overnight (10 h) until dry.

[0035] (4) The dried mixed powder was placed in a small porcelain boat and heat treated in a tubular furnace in an Ar atmosphere. The temperature was raised to 700°C at a heating rate of 5°C / min, and the temperature was kept for 6 hours. The mixture was naturally cooled to room temperature and the sample was collected. The obtained product was labeled as MoO2 / MoS2-0.5.

[0036] Example 2

[0037] The difference from Example 1 is that the MoCl5 in step (2) is changed to 1g, and the obtained calcined product is marked as MoO2 / MoS2-1 sample; the rest is the same as Example 1.

[0038] Example 3

[0039] The difference from Example 1 is that the MoCl5 in step (2) is changed to 1.5 g, and the obtained calcined product is marked as MoO2 / MoS2-1.5 sample; the rest is the same as Example 1.

[0040] Comparative Example 1

[0041] The difference from Example 1 is that the calcination temperature in step (2) is changed to 800°C, and the obtained calcined product is marked as MoO2 / MoS2-800 sample; the rest is the same as Example 1.

[0042] Comparative Example 2

[0043] The difference from Example 1 is that the calcination temperature in step (2) is changed to 900°C, and the obtained calcined product is marked as MoO2 / MoS2-900 sample; the rest is the same as Example 1.

[0044] Comparative Example 3

[0045] The difference from Example 1 is that the molybdenite powder in step (1) is changed to commercial MoS2 powder, the calcination temperature in step (2) is changed to 900°C, and the obtained calcined product is marked as MoO2 / MoS2-900-1 sample; the rest is the same as Example 1.

[0046] Comparative Example 4

[0047] The difference from Example 1 is that step (2) is eliminated, that is, MoCl5 is not added for hybridization, and the obtained sample is denoted as MoS2-2; the rest is the same as Example 1.

[0048] Electromagnetic absorption characteristics test:

[0049] Absorption performance study: The prepared natural molybdenite with electromagnetic wave absorption performance of molybdenum disulfide nanosheet array was taken as a sample, and the electromagnetic parameters of the material were tested using a vector network analyzer (VNA, Agilent N5234A, 8.2-12.4GHz, 12.4-18GHz). The specific method is: paraffin wax and sample are mixed in a mass ratio of 3:7, and pressed into 22.86×10.16mm block and 15.8×7.9mm block samples for testing, and the reflection loss value (absorption performance, RL) is simulated using software.

[0050] Depend on Figure 1 It can be seen that the MoO2 / MoS2-0.5, MoO2 / MoS2-1, and MoO2 / MoS2-1.5 composite materials obtained in the present invention are represented by MoO2 (PDF#32-0671) and MoS2 (PDF#37-1492) as the main phases. The wave absorption performance curve of the MoO2 / MoS2-0.5 composite material obtained in Example 1 is as follows: Figure 2 As shown, the numbers in the legend represent the reflection loss values ​​at different thicknesses. RL of MoO2 / MoS2-0.5 composite material min Reaching -47.61dB (f is 9.29GHz, d is 1.7mm), with the change of d, its EAB can cover the entire X and Ku bands (the frequency width of RL<-10dB, indicating the effective absorption width, representing the frequency range that can absorb 90% of the energy electromagnetic waves). Figure 3 As shown, with the change of d, the RL of the MoO2 / MoS2-1 composite material in Example 2 minThe absorption performance and absorption width of the wave absorption are both below the standard of effective absorption. Figure 4 As shown, with the change of d, the RL of the MoO2 / MoS2-1.5 composite material in Example 3 min The absorption performance and absorption width of the wave absorption are not up to the standard of effective absorption. Figure 5 As shown in the figure, with the change of d, the RL of the MoO2 / MoS2-800 composite material in the comparative example 1 min -8.9dB, its absorption performance and absorption width do not meet the standard of effective absorption. Figure 6 As shown in the figure, with the change of d, the RL of the MoO2 / MoS2-900 composite material in the comparative example 2 min The value is -9.7dB, and its absorption performance and absorption width do not meet the standard of effective absorption. Comparative Examples 1 and 2 show that temperature has an effect on the absorption performance of the sample. Figure 7 As shown in Figure 2, with the change of d, the RL of the MoO2 / MoS2-900-1 composite material in Comparative Example 3 min The absorption performance and absorption width of the sample are -3.7dB, which does not meet the standard of effective absorption. This shows that the absorption performance of the sample prepared by commercial MoS2 is poor compared with molybdenite. Figure 8 As shown, with the change of d, the RL of the MoS2-2 composite material in comparative example 4 min The frequency bandwidth is -11.5dB, which meets the standard of effective wave absorption. However, the frequency bandwidth is smaller than that of Example 1, indicating that heat treatment in a muffle furnace under air atmosphere can slightly improve the wave absorption performance of the material, but the degree of improvement is limited. By comparing Examples 1, 2, 3, and 4, it can be seen that oxygen doping can improve the wave absorption performance of molybdenite in air atmosphere, but the degree of improvement is limited. 5+ Self-doping can greatly improve the wave absorption performance of the material, which shows that 2- and Mo 5+ After step-by-step hybridization, excellent microwave absorption performance can be achieved. At the same time, commercial MoS2 did not achieve the desired effect after the same process, which shows that natural molybdenite is more suitable as the raw material of this process for preparing microwave absorbing materials.

[0051] The description of the above specification and embodiments is used to explain the protection scope of the present invention, but does not constitute a limitation on the protection scope of the present invention. Through the enlightenment of the present invention or the above embodiments, ordinary technicians in this field can obtain modifications, equivalent substitutions or other improvements to the embodiments of the present invention or part of the technical features thereof through logical analysis, reasoning or limited experiments, which should be included in the protection scope of the present invention.

Claims

1. A method based on O 2- and Mo 5+ The method for preparing microwave absorbing powder by step-by-step hybridization of natural molybdenite is characterized by: The following steps are involved: 1) Place molybdenite in a muffle furnace for heat treatment to obtain O-MoS (2-x) Composite materials; 2) stirring the composite material obtained in step 1) and MoCl5 in deionized water; 3) placing the mixture obtained in step 2) in a drying oven overnight until dry; 4) The dried mixture obtained in step 3) is heat treated in a tubular furnace in an Ar atmosphere and naturally cooled to room temperature to obtain a MoO2 / MoS2 composite absorbing material.

2. The preparation method according to claim 1, characterized in that: In the step 1), the heat treatment temperature is 400-500° C., and the heat treatment time is set to 2-4 hours.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the molybdenite, MoCl5 and deionized water is 1:0.5 to 1.5:

10.

4. The preparation method according to claim 1, characterized in that: The stirring in step 2) is magnetic stirring, the speed is 150-180 rpm, and the stirring time is 30-60 min.

5. The preparation method according to claim 1, characterized in that: In the step 3), the temperature of the drying oven is 80-100° C. and the drying time is 8-16 hours.

6. The preparation method according to claim 1, characterized in that: In the step 4), the temperature is raised to the calcination temperature at a heating rate of 5 to 10° C. / min, the heat treatment temperature is 700 to 800° C., and the holding time is 6 to 8 hours.

7. A method according to claim 1 based on O 2- and Mo 5+ The microwave absorbing material prepared by the step-by-step hybridization method of natural molybdenite is characterized by: Using natural molybdenite as raw material, through heat treatment process, O 2- and Mo 5+ The natural molybdenite was hybridized step by step to realize the preparation of MoO2 / MoS2 composite absorbing materials.

8. Use of the absorbing material according to claim 6 as an electromagnetic wave absorbing material.

Citation Information

Patent Citations

  • Oxygen-doped molybdenum disulfide thermoelectric material preparation method

    CN106898691A